Role of Iron Metabolism in Breast Cancer Patients - Dhankhar, Rakesh; C, Adarsh; Dahiya, Kiran; Ghalaut, Veena Singh; Nityasha; Dhull, Anil Kumar; Khurana, Anil (Cancers Review, 2014)
Iron metabolism is closely related to carcinogenesis. In this study, iron, ferritin and TIBC were analysed in 30 patients of early stage, 30 of advanced stage breast carcinoma before and after treatment and the results were compared with 30 healthy controls. The levels of all the three parameters were found to be significantly higher in breast cancer patients as compared to healthy controls and patients with advanced disease showed greater values as compared to early stage disease. These levels decreased after treatment and the difference was more significant in patients with complete response. Serum analyses of iron, ferritin and TIBC may help in assessing the severity and prognosis of the disease.